Islamic Law Aspect on in Valuation and Execution Intellectual Property (IP) Asset as Bank Collateral in Creative Economy - Margono, Suyud (International Journal of Social Science Research and Review, 2024)
One of the issues faced by many creative economy actors in this relatively newly established industry is the lack of supporting infrastructure, such as the limited access to financing and one of the prominent issues is banks’ reluctance to accept intellectual property (“IP”) as collateral to secure loans including problems concerning valuation of IP Asset as Collateral which has implications several regulation concerning Intellectual Property. In the spirit of furthering the creative economy, the Government has recently issued Government Regulation Number 24 of 2022 on Intellectual Property-Based Creative Economy Financing. This matters includes in relation with IP assets that are exposed and exploited their product (goods or services) on the basis of exclusivity in financing and loan contractual scheme as collateral. This article normative legal research in which intended for studies that are literary and practical works which is Intellectual Property (IR) system in relation with valuation and execution as bank collateral either Indonesia prevailing law and Islamic (Syariah) Law. The result of this research that IP owners often deal with complex contractual relationships that involve different forms of cooperation in research, production or commercialization. most important aspect concerning capacity and competency with comprehensive knowledge deal with IP Asset as Collateral before Banks, and others financial institution, execution of guarantees as applied to Islamic banking has adopted many syariah law, in the practice, there are still many problems the implementation of guarantees as applied to Islamic banking has adopted many Islamic laws. However, in the practice, there are still many problems that arise from the Islamic law scope the concept of justice and the philosophy of maslahah.
Keywords: Creative Economy Valuation and Execution Asse; Intellectual Property (IP) Collateral; Islamic (Syariah) Law

Summary survey on publishing contract in the OAPI space - Ngombé, Laurier Yvon (The Journal of World Intellectual Property, 2024)
The OAPI member states constitute a space for theharmonization of copyright in Africa. This harmonizationis yet to be completed, as attested by the conventionalrules relating to the publishing contract. In addition,investigating about the publishing contract in the OAPIspace requires an examination of both the text of theBangui Agreement and that of the national laws of the 17member states. Some differences must be pointed outkeeping in mind the question of possible conflict of laws.
Published by John Wiley & Sons Ltd.
Keywords: ARIPO; Conflict of laws; Contract; Copyright